Community-based behavioral health interventions: Developing strong community partnerships. (April 2019) - McNeish, Roxann; Rigg, Khary K.; Tran, Quynh; Hodges, Sharon
Highlights: Building trust was essential to developing productive and cohesive working relationships. Clarifying each partner's role on the coalition promoted accountability as partners were clear about their responsibilities. Selecting partners based on their unique skillsets ensured coalitions had partners with complementary strengths. We found that having clear governance and decision-making structures were key to having strong partnerships. This study adds to the limited amount of empirical data on best practices for developing community partnerships. Abstract: The popularity of community-based interventions has experienced a revival over the last two decades. The general theme behind this trend is that greater community involvement provides researchers and practitioners with culturally relevant information to make interventions successful. This involvement is usually solicited through the formation of community coalitions and advisory boards. Although the positive influence of community partnerships is well established, strategies for successfully developing and sustaining these partnerships are less clear. To address this gap, this paper presents evaluation findings from The Making Connections Initiative, a national effort emphasizing community-level prevention strategies for improving the mental health of men/boys. Sixteen grantees were tasked with developing a coalition of community organizations to provide input into the development and implementation of a local prevention initiative. An evaluation of the 16 grantees' planning activities identified four themes related to developing and sustaining successful community partnerships. This article reports on the strategies that were found most successful across grantees. With the increasing popularity of community-based programs, strategies for successfully partnering with local organizations are particularly important. This study adds to the limited research on best practices for forming community partnerships and should serve as a guide for community-based evaluators and program planners.